STRATEGI PEMASARAN PRODUK GADAI SYARIAH DALAM MENARIK MINAT NASABAH DI MASA PANDEMIK COVID-19 (PEGADAIAN SYARIAH CABANG PRENDUAN SUMENEP MADURA) - JUMARI .; MASHURI TOHA (LP2MTBM MAKARIOZ, 2021)
The development of Islamic financial institutions, one of which is sharia pawnshops in Indonesia, is so significant, even thesharia service units of the pawnshops themselves are easy to find in various cities in Indonesia. This study aims to determinethe marketing strategies carried out by PT Pegadaian Syariah and what products are offered by the Prenduan Branch ofSharia Pegadaian. The method chosen in this study is qualitative to examine more deeply about the tricks, methods,techniques and methods. From the results of the study found several strategies implemented at the Prenduan branch officeof the Prenduan Sharia Pegadaian, including, 1) Social Media Marketing, here the pawn party utilizes the internet, becausethe features provided by this social network are very helpful in marketing products and services to the public. . 2) Door ToDor, this is also done by pawnshops to visit residents' homes to introduce their products and services. 3) Making banners orbrochures, to distribute this is also done by the pawnshop in marketing their products, when we see it on the road we will finda large banner that is clearly visible about sharia pawnshops, or employees also take to the field to distribute brochures withcheap promotions with there is a big discount at the end of the year. 4) Expanding the Network of Relations with the MassMedia, this is also important in building relationships with the mass media. So that it can help in reaching the nationalmarket.